Konsentrasi Logam Berat Khromium (Cr) pada Air, Sedimen dan Kerang Darah (Anadara granosa) di Perairan Sungai Morosari dan Sungai Gonjol Kecamatan Sayung Kabupaten Demak - Setiawan, Kharis; Maslukah, Lilik; Pribadi, Rudhi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
The waters of Morosari and Gonjol River is along the stream has been utilized for various activities such as industry, agriculture and local resident. Measurement of the concentrations of Cr in a water, sedimens, and cockles showed in the period of june 2010 as a whole is below the limit of AAS accuracy <0.01 mg/l (in the water of Morosari and Gonjol River). Cr metal Concentrations in water ranges from 0.04 to 0.29 mg/l at Morosari River and 0.09 to 0.22 mg/l at Gonjol River in July 2010. The Cr concentrations in sedimens ranges from<0.01 to 6.26 mg/kg at Morosari River and <0.01 to 9.810 mg/kg in Gonjol River. The Cr Concentrations in the cockles were below the limit of AAS accuracy <0.01mg/kg. Cr concentrations in water on June 2010 based on the Decree of Minister of Environment No. 51 Year 2004 were uncertainty, but Cr concentrations in period of July 2010 were above the limit 0,005 mg/l for marine biota and 0,002 mg/l for marine tourism. While in the sediments, referring to the quality standard set by the Ontario’s Ministry of Environment of Canada, the Cr concentrations were above the maximum limit (0.11 mg/kg) in other word, the sediments were heavily polluted. But in the soft tissue of Cockles (Anadara granosa), Cr concentrations were below the limit (<0.01 mg/kg), it means the Cockles still are unpolluted yet.